Examining testlet effects in the TestDaF listening section: A testlet response theory modeling approach. (January 2014) - Eckes, Thomas
Testlets are subsets of test items that are based on the same stimulus and are administered together. Tests that contain testlets are in widespread use in language testing, but they also share a fundamental problem: Items within a testlet are locally dependent with possibly adverse consequences for test score interpretation and use. Building on testlet response theory (Wainer, Bradlow, & Wang, 2007), the listening section of the Test of German as a Foreign Language (TestDaF) was analyzed to determine whether, and to which extent, testlet effects were present. Three listening passages (i.e., three testlets) with 8, 10, and 7 items, respectively, were analyzed using a two-parameter logistic testlet response model. The data came from two live exams administered in April 2010 ( N = 2859) and November 2010 ( N = 2214). Results indicated moderate effects for one testlet, and small effects for the other two testlets. As compared to a standard IRT analysis, neglecting these testlet effects led to an overestimation of test reliability and an underestimation of the standard error of ability estimates. Item difficulty and item discrimination estimates remained largely unaffected. Implications for the analysis and evaluation of testlet-based tests are discussed.